Respuesta :
Answer:
Average rate of change for given function is: -2
Step-by-step explanation:
Given function is:
[tex]f(x)=x^2-6x+8\\x_12= 1\\x_1 = 3[/tex]
In order to find the rate of change, we have to find the value of function on x1 and x2
So,
[tex]f(x_1) = (3)^2-6(3)+8 = 9-18+8 = -1\\f(x_2) = (1)^2-6(1)+8 = 1-6+8 = 3[/tex]
The formula for finding the rate of change is:
[tex]Rate\ of\ change = \frac{f(x_2)-f(x_1)}{x_2-x_1}[/tex]
Putting the values, we get
[tex]=\frac{3-(-1)}{1-3}\\=\frac{3+1}{-2}\\=\frac{4}{-2}\\= -2[/tex]
Hence,
Average rate of change for given function is: -2
Answer:
Average rate of change for given function is: -2
Step-by-step explanation: